OFFICE CHANNELING AND ITS IMPACT ON THE PROFITABILITY OF ISLAMIC BANK - Arif, M. Nur Rianto Al; Rahmawati, Yuke (Universitas Brawijaya, Indonesia, 2017)
The purpose of this paper is to analyze that the office channeling policy that based on Bank Indonesia's rule no. 8/3/PBI/2006 had an on the profitability of Islamic banking industry in Indonesia. This research used ordinary least square regression to analyze the impact that office channeling as a dummy variable in this model. The result showed that office channeling didn't have a bearing on the profit rate of Islamic banking industry that measured. According to from this result, either regulator, parent's bank, and Islamic business unit had the obligation increase the socialization, education, and services to the customers